COMPARISON OF THE ANTIOXIDANT ACTIVITIES OF PURPLE SWEET TABS (Ipomoea batatas L.) LEAVES WITH DPPH METHODS FROM SIDRAP AND ENREKANG AREA - Qurrata'yuni, Nuril Qurrata'yuni (Makassar Natural Product Journal (MNPJ), 2024)
Purple Sweet Potato Leaves (Ipomoea batatas L.) is included in the Convolvulaceae family which has properties as an antioxidant that can prevent disorders of liver function, lower blood sugar levels, and prevent free radicals. Purple sweet potato leaves contain alkaloids, flavonoids, saponnins, steroids, terpenoids, tannins, and phenols. The purpose of this study was to determine differences in antioxidant activity and the value of antioxidant activity based on the location of growth using the (2,2 Diphenyl -1-Pikrylhidrazyl/DPPH) method as measured by a UV-Vis spectrophotometer at a maximum wavelength of 515 nm. Quercetin is a class of flavonoids used as a comparison. Extraction of purple sweet potato leaves by maceration method using 96% ethanol solvent. The results showed that the antioxidant activity of purple sweet potato leaves from sidrap was 91.178 µg/mL and that from enrekang was 95.909 µg/ml, so it can be concluded that purple sweet potato leaves from enrekang had high antioxidant activity compared to purple sweet potato leaves from sidrap.